2016
DOI: 10.3344/kjp.2016.29.3.164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spinal Dopaminergic Transmission in the Analgesic Effect of Nefopam on Rat Inflammatory Pain

Abstract: BackgroundNefopam has been known as an inhibitor of the reuptake of monoamines, and the noradrenergic and/or serotonergic system has been focused on as a mechanism of its analgesic action. Here we investigated the role of the spinal dopaminergic neurotransmission in the antinociceptive effect of nefopam administered intravenously or intrathecally.MethodsThe effects of intravenously and intrathecally administered nefopam were examined using the rat formalin test. Then we performed a microdialysis study to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, in animals with high inflammation at the zenith of clinical scores (at D13), nefopam slightly reduced the pain score. Nefopam has been shown to have antinociceptive effects on rodents ( 8 , 9 ), so its administration should decrease arthritis-induced pain perceived by animals and may also lead to a higher level of mobility. A previous study has demonstrated a correlation between nefopam administration and improvement of motor coordination ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in animals with high inflammation at the zenith of clinical scores (at D13), nefopam slightly reduced the pain score. Nefopam has been shown to have antinociceptive effects on rodents ( 8 , 9 ), so its administration should decrease arthritis-induced pain perceived by animals and may also lead to a higher level of mobility. A previous study has demonstrated a correlation between nefopam administration and improvement of motor coordination ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nefopam is an antinociceptive compound, part of benzoxazocine class drugs, which acts centrally at spinal and supra-spinal sites ( 8 ). Therefore, it acts through different mechanisms of action compared to NSAID or opioids ( 9 ). Even though its mechanism of action is not fully understood, nefopam seems to be involved in the inhibition of reuptake of monoamines (norepinephrine, serotonin, and dopamine) in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…27 Several studies have demonstrated the anti-nociceptive effects of nefopam using a variety of routes of administration and for various indications. [9][10][11][28][29][30] Nefopam reduced thermal hypersensitivity after acute and postoperative pain in rats. 31 Intraperitoneal nefopam showed an antiallodynic effect mediated by adenosine triphosphate-sensitive potassium channel in rats with spinal nerve ligation-induced neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the serotonin, which mainly affects the CNS, analgesic pathway mediated by nefopam-induced activation of the dopamine receptors, has not been elucidated. However, according to animal study, dopaminergic analgesic pathway by nefopam is not observed at the spinal level and may be possible at the supraspinal level [ 26 ].…”
Section: Discussionmentioning
confidence: 99%